Hubungan Antara Konsep Diri dan Dukungna Sosial Dengan Kecemasan Sosial Pada Siswa Kelas X Listrik di SMK Negeri 2 Medan - Sabrini Mentari Rezeki; Muhammad Rajab Lubis; Abdul Munir (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2021)
The objectives of this study are 1) The relationship between self -concept and social anxiety in students of class X Listik in SMK Negeri 2 Medan. 2) The relationship between social support and social anxiety in students of class X Electricity in SMK Negeri 2 Medan. 3) The relationship between self -concept and self -esteem with social anxiety in students of class X Electricity in SMK Negeri 2 Medan. This type of research is a quantitative approach with correlational methods. Correlation research method is used to detect the extent of variations in a factor related to variations in one or more other factors based on the correlation coefficient. and the sample in this study was 90 students. Based on the results of the discussion of this study shows 1) There is a relationship between self -concept and social anxiety of students of class X Electric SMK Negeri 2 Medan. This conclusion is obtained and the result of the calculation is the calculated value = 4,669. 2) There is a relationship between social support and social anxiety of students of class X Listrik SMK Negeri 2 Medan. This conclusion is obtained from the results of the calculation that is the calculated value = 7,783 at the alpha level of 5%. 3) There is a relationship between self-concept and social support collectively to students' social anxiety. This conclusion is obtained from the calculation results that is the value of Fhitung = 39, 735.